Análise termoelástica de placas de Reissner via método dos elementos de contorno - Silva, Arthur Leandro de Azevedo (2019)
This work presents a boundary element formulation for the analysis of shear deformable plates under three types of loads: temperature variation, linear load distribution and reactions from Winkler’s foundations. The elastic and thermal behaviors were considered uncoupled, this way, the thermal variation interferes with the mechanical behavior, while the stress and strain distributions have no influence in temperature fields. Temperature change at the plate mid surface results in axial stresses that are estimated through the theory of elasticity applied to membrane elements in plane stress distribution. Thermal gradients through the plate’s section (from top to bottom surface) result in stresses and strains that can be estimated through Reissner’s theory for shear deformable plates. Linear loads distributions are considered in the analysis as forces in a perpendicular direction of the plate’s midsection. Reactions from Winkler’s foundations are considered, resulting in a linear system composed by boundary and internal domain variables. In the numerical implementation used, the system of equations is composed by the integration of boundary quadratic elements and triangular linear cells in the domain for the coupling of the thermal load, surface forces and Winkler’s spring reactions. Results are presented through examples for analytical validation and also to demonstrate the program applicability in the scope of civil engineering.